The Study of the Kangen Yogyakarta Market from the Viewpoint of a Traveler Experiencing the Culinary Festival - Suci Sandi Wachyuni; Kadek Wiweka; Mohammad Rizky Ferdinandsyah; Nenny Wahyuni (STIE Pariwisata API Yogyakarta, 2023)
Culinary is intricately connected to the creation of processed foods and beverages that are characteristic of a certain region. In Indonesia, a diverse range of gastronomic delights with distinct flavors may be found from Sabang to Merauke. Nevertheless, the swift advancement of technology in the culinary domain has led to novel breakthroughs in the creation of food and drink items, which have the potential to alter the presence of traditional local cuisine. In order to prevent the marginalization of local cuisine, several strategies are implemented to promote it, one of which is organizing a festival. Every year, Yogyakarta has a Pasar Kangen Festival. This festival has the capacity to